2019
DOI: 10.35826/ijoess.2406
|View full text |Cite
|
Sign up to set email alerts
|

Humour Styles and Critical Thinking Dispositions in Adolescents

Abstract: Humour and critical thinking are two concepts that fosters and generates each other; therefore they cannot be thought separately from each other. These two concepts together are the most significant and effective skills that can be used in evaluating the cognitive development. From this point of view, this study was conducted to examine the relationship between the humour styles and critical thinking dispositions of adolescents. This was a descriptive study in correlational screening model. 'Humour Styles Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In this framework, there is a strong and meaningful relationship between possessing critical thinking skill and the tendency to use the critical thinking skill (Facione, 2000). However, it should be kept in mind that critical thinking disposition is not the same as the critical thinking skill, but is rather complementary to the critical thinking skill (Cesur and Yaralı, 2019). In their study, McGrath (2003), Shin et al (2006) and Yang and Chou (2008) found a positive relationship between critical thinking skills and the critical thinking dispositions.…”
Section: Conceptual Frameworkmentioning
confidence: 93%
“…In this framework, there is a strong and meaningful relationship between possessing critical thinking skill and the tendency to use the critical thinking skill (Facione, 2000). However, it should be kept in mind that critical thinking disposition is not the same as the critical thinking skill, but is rather complementary to the critical thinking skill (Cesur and Yaralı, 2019). In their study, McGrath (2003), Shin et al (2006) and Yang and Chou (2008) found a positive relationship between critical thinking skills and the critical thinking dispositions.…”
Section: Conceptual Frameworkmentioning
confidence: 93%